ETIKA PEGAWAI KANTOR DALAM PERSPEKTIF ISLAM: IMPLEMENTASI NILAI-NILAI AKHLAKUL KARIMAH DI LINGKUNGAN KERJA - Alfera Rahmawati; Anik Faseha; Nasrun Harahap (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Employee ethics are an important factor that supports the creation of a positive work culture foundation and can improve employee professionalism in an organization, institution, or office. The purpose of this study is to determine the ethics of office employees from an Islamic perspective and the implementation of moral values ​​in the work environment, the research method used is a qualitative descriptive approach through library research, the results of the study show 1) Office employee ethics are moral and behavioral guidelines that must be adhered to by every worker in carrying out their professional duties, 2) in Islam, ethics are closely related to moral science, which is a discipline that discusses various moral virtues and how to obtain them so that humans can adorn themselves with commendable qualities, 3) Akhlakul Karimah is a rule or norm that regulates the relationship between humans, God and the universe, Akhlakul Karimah is interpreted as a commendable trait or good deeds. Akhlakul Karimah shows the perfection of a person's faith in Allah SWT. which includes the noble character in Islam, namely, patience, sincerity, humbleness, honesty, trustworthiness, forgiveness and contentment, 4) The code of professional ethics is a norm that is accepted and applied by a professional group to provide guidance to its members regarding the behavior that should be.